A short report on tooth replacement in an older suburban population in Nigeria (2017)
To determine: the knowledge of the participants about removable dentures, importance of tooth replacement; prevalence of tooth loss and denture use; and factors associated with its non-use among an elderly population in Nigeria. Tooth loss without replacement can impact negatively on the quality of life of the elders, thus making use of denture a basic requirement for those with partial or complete edentulous arches in developed countries. It is, however, not known if this is the case among elders in suburban Nigeria. A cross-section of 392 consenting elderly participants aged ≥65 years residing at Idikan, Ibadan, Nigeria, were interviewed on their biodata, knowledge of removable denture and importance of tooth replacement, history of use of denture and reasons for non-use where applicable. Oral examinations for the presence of missing teeth and denture were conducted by an examiner. Data were analysed with SPSS and P value set at ˂.05. The mean age of the participants was 73 (SD = 9.2) years. About 39% of the participants believed that it was important to replace missing teeth, 56.0% had poor knowledge about tooth replacement options, and 47.7% had at least a missing tooth. Only 7.1% of those with missing teeth had them replaced and all were using removable acrylic partial dentures. Financial constraint was the main reason for non-replacement of missing teeth (80.1%). Age, gender, occupation before retirement, income, level of education and presence of physical impairment were associated with non-use of denture (P ˂ .05). Many elderly individuals had poor knowledge about removable dentures and the importance of tooth replacement. About half of the participants had full complement of teeth and only 7.1% of those with tooth loss reported denture wear. Major reasons for non-use of dentures were due to economic reasons.